STUDY ON REGISTRATION AND REGULATORY REQUIREMENTS FOR VACCINES IN USA, EUROPE AND CANADA - Shoukat Ali; Shanthakumar GS; Shrikanth P; Ayushi Agrawal; Navya BR (Journal of Biomedical and Pharmaceutical Research, 2020)
In recent years vaccines are the foremost necessary health intervention globally. An immunizing agent could also be a biological preparation that will increase the immunity to a specific wellness. The development of an immunizing agent could be a posh and tedious method. A strict regulatory guidelines used to figure out the protection, efficacy, and quality should be achieved throughout the development of a vaccine for its authorization. In USA biologics were regulated by the Centre for Biologics Evaluation and Research (CBER) beneath USFDA. In Europe, European Medicines Agency (EMA) regulates the biologics and authorization is granted by the European Commission (EC). In Canada, vaccines are regulated by Biologics and Genetics Therapy Directorate (BGTD) under Health Canada (HC). For Registration of vaccine, Biologics license application (BLA) in USA, marketing authorization application (MAA) in EU and New Drug Submission (NDS) Application in Canada ought to be submitted. While registration of a vaccine, post-marketing surveillancestudies such as VAERS should be done in USA, Pharmacovigilance system in Europe and Canadian Adverse Events Following immunization surveillance system (CAEFISS) in Canada monitors the safety of a vaccine.